That's not what I meant! : how conversational style makes or breaks relationships - Tannen, Deborah (New York : Ballantine, 1987)
Often it's not what you say, but how you say it, that counts. Deborah Tannen, the internationally-acclaimed expert on communication and author of the bestselling YOU JUST DON'T UNDERSTAND, will help you recognize your own conversational style and how it meshes or clashes with the styles of others. Entertaining and informative, everyone who speaks will want to read this gem. Often it's not what you say, but how you say it, that counts. Deborah Tannen, the internationally-acclaimed expert on communication and author of the bestselling YOU JUST DON'T UNDERSTAND, will help you recognize your own conversational style and how it meshes or clashes with the styles of others. Entertaining and informative, everyone who speaks will want to read this gem.
Linguistics and conversational style -- Problem is the process -- Workings of conversational style -- Conversational signals and devices: Conversational signals -- conversational devices at work -- conversational strategies: Why we don't say what we mean: Why we won't say what we mean -- Framing and reframing -- Power and solidarity -- Talking at home: conversational style in close relationships -- Why things get worse.
Includes index.
Bibliography: p. 199-201.
Keywords: Conversation; Interpersonal communication